What is the risk of European sovereign debt defaults? Fiscal space, CDS spreads and market mispricing of risk - Joshua Aizenman; Michael Hutchison; Yothin Jinjarak (University of California, Economics Department, 2011)
We estimate the pricing of sovereign risk for a large number of countries within and outside of Europe, before and after the global financial crisis, based on fiscal space and other economic fundamentals. We measure how accurately the model predicts CDS spreads based on fundamentals, and determine whether the model explains spreads equally well in the Euro zone countries, and the PIIGS in particular, as elsewhere in the world. We validate that fiscal space has been an important determinant of market-based sovereign risk, and find evidence of mispricing in PIIGS given current fiscal space and other current fundamentals: unpredicted low CDS in tranquil period and unpredicted high during global crisis period, especially 2010 when sovereign debt crisis swept over Euro area. To gain further insight, we match the PIIGS with 5 middle income countries outside Europe that, before the crisis (2007), were closest in terms of fiscal space (debt/tax). We find that PIIGS default risk is priced much higher than the matched countries in 2010, even allowing for differentials in fundamentals. A possible interpretation of this finding is that the market is pricing not on current fundamentals but future fundamentals, expecting the PIIGS fiscal space to deteriorate markedly. The adjustment challenges of the PIIGS may be viewed as economically and politically more difficult due to exchange rate inflexibility that is not a constraint in the matched group of the middle income countries.
Keywords: E43; F30; G01; H63; 330; CDS spreads; sovereign risk; fiscal space; PIIGS and the Euro area; fiscal space; Finanzmarktkrise; Öffentliche Schulden; Insolvenz; Risiko; Welt